Description of antibiotic therapy of hospitalized-community-acquired pneumonia in PKU Muhammadiyah Gamping hospital - Joko Sudibyo; Akrom Akrom (Pharmaciana, 2022)
Long-term administration of IV antibiotics risks increasing treatment costs and patient morbidity, but until now, intravenous (IV) antibiotics are still the most comprehensive choice in treating community pneumonia inpatients in hospitals. The purpose of this study was to describe the use of antibiotics and duration of AB replacement from IV administration to oral administration (P.O) in community-acquired pneumonia (CAP) patients at PKU Muhammadiyah Gamping Hospital (PMGH). This study used a cross-sectional design. Data were collected prospectively by purposive sampling. Inclusion criteria were hospitalized patients with CAP who received AB IV therapy for 24-72 hours. Patients with lung cancer or sepsis were excluded. Data were collected from medical records, laboratory examination records, and drug administration. Data were analyzed univariately. The number of 38 patients according to the criteria with a mean age of 59.8 ± 12.7 years; most were male (55.3%) and comorbid with heart failure (13.2%). The mean length of hospitalization was 4.9 ± 1.6 days. Most of the patients received Cephalosporins antibiotic group, either given IV (89.5%) or P.O. (78.1%); the rest received the quinolone group. The mean time of changing AB from IV to oral administration was 134.25 ± 15.98 hours. Most inpatient CAP patients at PMGH received a cephalosporins group, either IV or orally.